Insight into the deactivation and regeneration of HZSM-5 zeolite catalysts in the conversion of dimethyl ether to olefins - Cordero-Lanzac, Tomás; Ateka, Ainara; Pérez-Uriarte, Paula; Castaño, Pedro; Aguayo, Andrés T.; Bilbao, Javier (American Chemical Society, 2018)
The impact of different process variables affecting the coking and rejuvenation of HZSM-5 zeolite catalyst has been studied during the conversion of dimethyl ether (DME) to olefins in a fixed bed reactor. Those variables involve the effect of (i) the matrix material with mesopores; (ii) temperature; (iii) space time; (iv) acidity of the catalyst; (v) steam, inert or air in the reaction-regeneration medium. Used catalysts have been characterized through N2 adsorption-desorption and temperature-programmed oxidation and the presence of three coke fractions has been identified deposited within the zeolite micropores, the external surface of the crystals and the mesopores of the matrix. Low Si/Al ratios (140) and temperatures (350 ºC), and co-feeding water with DME, reduce the formation of coke within the zeolite micropores, favoring the stability of the catalyst. Reaction-regeneration cycles confirm that catalysts totally recover the activity through combustion of coke during a heating ramp up to 550 ºC.
https://openpolicyfinder.jisc.ac.uk/id/publication/7779?from=single_hit
Keywords: Catálisis heterpgénea; Zeolitas; Hidrocarburos; Desactivación; Catalizadores; MTO; Ingeniería química